Predação de ninhos artificiais nas diferentes paisagens do bioma mata atlântica, no estado de São Paulo - Galvão, Camila André (2015)
The nest predation is an event that adversely affects the reproductive success of birds. One of the main theories explaining their population decline is the "Theory mesopredator release", especially in fragmented areas, where the chain of top predators are the first to go extinct, causing an increase in mesopredators in place, leading to an growth in nest predation and reduction of the bird population. In this context, estimate the nest predation, through the use of artificial nests is of paramount importance both in preserved areas, as fragmented, present in the vicinity of protected areas in order to know which are the natural predators of nests, estimates predation intensity, quickly, in different landscapes present in the Atlantic Forest biome. Thus, the artificial nests was sampled through the use of nests (artificial), each containing two nest eggs of domestic fowl Quail (Coturnix cotunix), and camera traps. In all study areas the cameras and the nests were placed together in the field (both at the top, as on the ground), so that predation records were provided by recording 30-second videos filmed by the cameras. In Carlos Botelho State Park (CBSP) gave a sampling effort 2100 cameras/night. It’s surrounding area analyzed, corresponding to the Agroforestry System (AS) provided 7200 cameras/hours sampling. As for the territorial portion of the Capão Bonito National Forest (NF) and its surroundings were sampled together, making an effort 1155 cameras/night. Several species of birds (10), reptiles (1) and mammals (7) were recorded preying on the eggs, accounting for an overall predation rate, for all fields of study, 42.6%. The CBSP obtained a 28.6% predation rate, corresponding to the rates in other areas as well preserved. Not so for NF he presented such a high rate (45.8%) as found in disturbed environments analyzed, AS and surrounding National Forest (100% and 65.5%, respectively). Among birds, the main predators were “Arapaçu de bico preto” (Dendrocolaptes platyrostris), “Falcão Relógio” (Micrastur semitorquatus) and “Macuco” (Tinamus solitarius), in Carlos Botelho State Park. In NF, the “Gralha-decrista- negra” (Cyanocorax chrysops), stood out as the main predator bird, and the “Gralha-Azul” (Cyanocorax caeruleus) for the AS. Among mammals, the CBSP the “Cuíca-de-quatro-olhos” (Philander frenatus) and the “Irara” (Eira barbara) were the most prominent. In NF, the "Javaporco" (Sus sp) became the dominant predator. In AS, the “Gambá-de-orelha-preta” (Didelphis aurita) was the only mammal predator. And for the group of reptiles, only the “Teiú” (Tupinambis merinae) did prey the nest in Carlos Botelho. In addition, depredations on the ground were the most abundant in all areas of study, corresponding 65% of predation compared to 35% of depredations on top, and during the daytime, corresponding to 77%. Thus, we can conclude that nests on the ground, depredations during the day, for bird species, corresponds to the profile of nest predators in the Atlantic Forest in the State of São Paulo. Nevertheless, the NF proved to be very close in terms of species composition and predation rate your anthropic environment. And the alternative of sustainable production, AS, resembled much of the damage also caused by conventional production of agricultural products (NF surroundings), in this case, the fauna of birds present in the Atlantic Forest.